2006
DOI: 10.2111/05-056r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Copper Supplementation in the Prevention of Molybdenosis in Cattle

Abstract: Revegetation and sustainable cattle grazing are major objectives in the reclamation of mine tailings at the Highland Valley Copper mine in British Columbia, Canada. A total of 150 cows with their calves grazed forage extremely high in molybdenum (Mo) for 5-6 weeks in the summer and fall for 3 consecutive years (2002-2004). The average stocking rate was 0.89 ha per animal unit month. The animals' diet consisted primarily of alfalfa (Medicago sativa L.) and orchardgrass (Dactylis glomerata L.) containing 100-400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Studies have shown however that residual Mo in the tailings is imbibed by vegetation and can accumulate to extremely high levels depending on the plant species and site , . Medicago sativa L. (alfalfa), a major forage at the Highmont site at HVC, accumulated 95−460 ppm Mo on a dry matter basis with no evidence of significant decreases in Mo since 1999, the year of establishment of plant cover at Highmont , . Animal health guidelines recommend a maximum level of 5 ppm Mo in feed for beef cattle .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown however that residual Mo in the tailings is imbibed by vegetation and can accumulate to extremely high levels depending on the plant species and site , . Medicago sativa L. (alfalfa), a major forage at the Highmont site at HVC, accumulated 95−460 ppm Mo on a dry matter basis with no evidence of significant decreases in Mo since 1999, the year of establishment of plant cover at Highmont , . Animal health guidelines recommend a maximum level of 5 ppm Mo in feed for beef cattle .…”
Section: Introductionmentioning
confidence: 99%
“…1, Table 2). The higher r 2 in 2004 compared with 2003 was attributed to decreased animal variability as 80% of the animals were new to the site in 2004 (Majak et al 2006). The parameter a of the In summary, the tissue elimination studies from 2003 and 2004 demonstrated that muscle and fat products from animals grazing Highmont could be used for human consumption one month after their departure from the site without significant tissue residues of Mo.…”
mentioning
confidence: 98%
“…Cattle grazing trials were conducted during [2002][2003][2004] on the reclaimed Highmont tailings pond at HVC to determine whether forage high in molybdenum (Mo) could sustain cattle grazing without ill effects to livestock. Forage levels of Mo in alfalfa (Medicago sativa L.) and orchardgrass (Dactylis glomerata L.) at the site ranged from 100 to 400 ppm and did not change significantly between years (Majak et al 2006). Dietary levels of Mo in excess of 10 ppm are considered toxic (Puls 1994).…”
mentioning
confidence: 99%
See 2 more Smart Citations